Prescription Opioid Misuse: Examining the Role of Opioid-Related Attitudes among Youth and Young Adults by Sexual Orientation. (1st July 2020) - Pitzer, Lindsay; Bennett, Morgane; Simard, Bethany; Schillo, Barbara A.; Vallone, Donna M.; Hair, Elizabeth C.
Abstract: Background : High prevalence of opioid misuse has been noted among youth and young adults—particularly among those who identify as lesbian/gay or bisexual (LGB). Yet, little is known about the relationship between opioid-related attitudes and misuse among those who identify as LGB. Objectives : This study examined the role of opioid-related attitudes (i.e. acceptance of misuse and risk perception) in relation to ever and past 6-month prescription opioid misuse, stratified by sexual orientation. Methods : This study used a nationally representative, probability-based sample of youth and young adults aged 15–34 ( N  = 12, 745; lesbian/gay = 398, bisexual = 857, heterosexual = 11, 490). Data were collected via online surveys in Spring 2018. Wald chi-square tests assessed differences in ever and past 6-month opioid misuse by sexual orientation identity. Weighted adjusted logistic regression models estimated the influence of opioid-related attitudes (acceptance of misuse and risk perceptions) in relation to ever and past 6-month opioid misuse, controlling for demographic characteristics, other past drug use, and psychosocial variables. Results : Logistic regression models indicated that attitudes related to the acceptance of opioid misuse was predictive of (a) higher odds of ever misuse among heterosexual and bisexual individuals and (b) higher odds of past 6-month misuse regardless of sexual orientation. Conclusions : Prescription opioid misuse among LGB youth and young adults may be addressed by shifting key attitudes surrounding opioids. To help stem this deadly epidemic, prevention efforts should be guided by the unique stressors facing the LGB community and focus on reducing the acceptability of misusing opioids.